EVALUATION OF ANTI-BACTERIAL ACTIVITY, GC/MS ANALYSIS AND GENOTOXIC POTENTIAL OF CARUM COPTICUM ESSENTIAL OIL FRACTIONS AGAINST MULTI-DRUG RESISTANT STAPHYLOCOCCUS AUREUS - S. A. Raja; M. Ashraf; A. A. Anjum; A. Javeed (Journal of Animal and Plant Sciences, 2016)
With the growing problem of emergence of multi-drug resistant bugs the surge for new treatment options has become inevitable. Essential oils contain combination of diverse nature of compounds that possess a variable range of antimicrobial activities. The current study aims to characterize the possible combination of bioactive constituents possessing appreciable activity against multi-drug resistant staphylococcus aureus. The essential oil was extracted using steam distillation and fractionated by silica gel gravity column chromatography using various solvent combinations in increasing order of their polarity. In-vitro antibacterial activity of essential oil and its fractions against multidrug resistant S. aureus isolates was performed by agar well and micro broth dilution methods. The toxicity of most effective fraction/s was evaluated by performing Comet assay on human lymphocytes. Finally the bioactive molecules present in the essential oil and its fractions were elucidated using GC/MS analysis. Results: Carum copticum essential oil and its fractions F1 was found effective against MDR S. aureus having zones of inhibition greater than the standards vancomycin and linezolid. Fraction F1 was more effective as the MIC values obtained in case of fraction F1 were lower than pure essential oil. Fraction F1 was found non-DNA damaging using Comet assay. Upon GC/MS analysis of essential oil thirty compounds were eluted with major constituents Carvacrol (24.4%), Ʈ -Terpinene (8.8%), Apiol (6.6%), Carvone (3.4%) and p-cymene (3.1%). Fraction F1 contained predominantly following compounds with highest concentration of Carvacrol followed by p-Cymene, Ʈ –Terpinene and Apiol as major constituents. It was concluded that Carum copticum essential oil fraction F1 with following constituents’ carvacrol, p-cymene, Ʈ-Terpinene and Apiol was the most effective fraction and have shown superior antibacterial activity as compared to pure essential oil.
Keywords: Carum copticum essential oil; multi-drug resistant Staphylococcus aureus; Minimum inhibitory concentration; Comet assay; GC/MS analysis